Accruals anomalies could be explained by the adverse selection risk induced by the information structure: the case of the Japanese securities market - Hiroaki Isoyama (Cogent Economics & Finance, 2024)
Accruals are regarded as investments in working capital and are an integral component in the growth process of firms. By assuming asymmetry of information among investors when predicting the returns on such investments, investors are exposed to adverse selection problems. Consequently, in market equilibrium, investors are believed to require compensation for the systematic risk associated with adverse selection exposure. By constructing the accruals factor as a variable to proxy for such risks, this study demonstrates that the accruals factor is priced and can enhance existing asset pricing models. Moreover, categorizing accruals into discretionary and non-discretionary components and constructing accruals factors from these components yields similar results. When the discretion of managers or market environment increases the degree of asymmetric information, adverse selection problems become more pronounced. Therefore, the accruals factor, serving as a proxy for the systematic risk associated with adverse selection, is an essential risk factor in asset pricing models. The accruals anomaly is a phenomenon that contradicts the EMH (efficient market hypothesis). This anomaly has been a compelling topic for accounting and finance scholars over the past quarter-century, as it pertains to fundamental issues, including the function of capital markets in pricing risk assets, allocating resources efficiently, and the institutional framework of information disclosure that affects the information environment of capital markets. While numerous studies have validated the robustness of this phenomenon, the reasons behind its occurrence remain unclear. Assuming the presence of information asymmetry among investors, as described by market microstructure theory, uninformed investors are exposed to the risk of adverse selection. To compensate for such risk exposure, it is believed that these investors require a risk premium. Empirical analyses using the GRS test, its Bayesian framework, and HJ-Distance (Hansen-Jagannathan-Distance) support this theoretical prediction. Excluding the role of the information structure when discussing market efficiency is akin to disregarding a crucial puzzle piece. Considering a more intricate structure makes it possible to rationally explain phenomena previously deemed anomalous. Therefore, it is believed that conducting analyses based on aspects of market microstructure theory, which specifically describe information asymmetry, is highly important for future research in accounting and finance.
Keywords: 330; Accruals anomaly; assetpricing; adverse selection; Fama-French 5- and 6-factor models; orthogonal decomposition; securities market; information asymmetry